2022
DOI: 10.1021/acs.langmuir.2c01137
|View full text |Cite
|
Sign up to set email alerts
|

Cr-Based MOF for Efficient Adsorption of Au at Low Concentrations

Abstract: The efficient enrichment and selection of Au are crucial for gold recovery. The adsorption technology is considered to have potential due to the advantages of operation simplicity and green processability. Nevertheless, the poor Au selectivity at low concentrations in complex solutions limits the further application of the adsorption technology. In this work, a novel Cr-based MOF adsorbent was successfully synthesized using 1,2,4-triazole and 4-aminobenzoic acid as ligands. Benefitting from the surface positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 51 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…The experimental data demonstrated that modified UKM-78 exhibits a significantly enhanced adsorption rate and efficiency, with a maximum adsorption capacity of 688.5 mg/g at pH 4.0. Compared to other reported materials for Au(III) adsorption (Figure 6c), 16,22,23 UKM-78 displayed a notably higher adsorption capacity. 24 To investigate the adsorption mechanism, we employed the Langmuir and Freundlich isotherm models, and their expressions are provided in S7 and S8.…”
Section: Adsorption Kineticsmentioning
confidence: 57%
See 2 more Smart Citations
“…The experimental data demonstrated that modified UKM-78 exhibits a significantly enhanced adsorption rate and efficiency, with a maximum adsorption capacity of 688.5 mg/g at pH 4.0. Compared to other reported materials for Au(III) adsorption (Figure 6c), 16,22,23 UKM-78 displayed a notably higher adsorption capacity. 24 To investigate the adsorption mechanism, we employed the Langmuir and Freundlich isotherm models, and their expressions are provided in S7 and S8.…”
Section: Adsorption Kineticsmentioning
confidence: 57%
“…Wang et al synthesized a Cr-based MOF using a one-pot method and achieved a high gold(III) adsorption capacity of 357 mg/g. 16 In contrast, postmodification entails attaching new organic ligands to the MOF precursors to enhance their functionality; however, this requires accessible modification sites on the MOF structure. 17 These strategies facilitate the introduction of specific functional groups, allowing the customization of MOFs with tailored properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41][42][43][44] Noteworthily, chromium-based MOFs have emerged as ultra-high water stable materials because of their robust metal-carboxylate bonds and rigid frameworks, leading to many applications of adsorption under practical conditions. 45,46 It should be noted that the molecular size of RhB exhibits unsimilarity with the pore size of traditional absorbents and a lack of strong attraction with the adsorption sites of the materials, resulting in a low adsorption efficiency of RhB. 47,48 Thus, it is necessary to incorporate negatively charged adsorption sites and achieve appropriate pore sizes within MOFs for significantly enhancing the adsorption capacity of the cationic RhB ions through efficient interactions.…”
Section: Introductionmentioning
confidence: 99%
“…39–44 Noteworthily, chromium-based MOFs have emerged as ultra-high water stable materials because of their robust metal-carboxylate bonds and rigid frameworks, leading to many applications of adsorption under practical conditions. 45,46…”
Section: Introductionmentioning
confidence: 99%